Emissão de elétrons por efeito de campo em dispositivos de grafeno - Tiago Campolina Barbosa (2012)
Since graphene was first isolated in 2004 by the micromechanical exfoliation of graphite, many research groups focused their works in studying the properties of this material. Graphene is a strictly bidimensional system very resilient to mechanical tension which presents high charge carriers mobilities, anomalous quantum hall effect observed even at room temperature and non vanishing conductivity even when the density of charge carriers approaches zero. Due to its high edge aspect ratio and to its excellent electrical conductivity, it is expected that graphene will be a wonderful field-emission device. In this work, we use the standard micromechanical exfoliation method of naturalgraphite to obtain single-layer graphene flakes over Si/SiO2 substrates. Graphene devices were fabricated by photolithography specifically for field emission measurements. We tried several fabrication methods and the results were evaluated. The devices were loaded in a vacuum chamber and I(V) curves were measured between the contacted graphene and a metallic anode. Our experimental results were fitted according to the Fowler-Nordheim theory and compared with the few recent works described in the literature.